2021
DOI: 10.1136/bmjopen-2020-046578
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of district health information system and its associated factors among health professionals working at public health facilities of the southwest of Ethiopia: cross-sectional survey

Abstract: ObjectivesTo assess utilisation of district health information system and its associated factors among health professionals in the southwest of Ethiopia, 2020.SettingPublic health facilities in the southwest of Ethiopia.ParticipantsA facility-based cross-sectional study was conducted among a sample of 260 participants.Main outcome measuresThe main outcome measure was utilisation of the district health information system.ResultsOverall, 149 (57.3%) of study participants had good utilisation of district health i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
3
10
3
Order By: Relevance
“…The finding was almost in line with a study finding in Hadiya Zone, Oromia Regional State, and Southwest Ethiopia, where utilisation of HMIS at health facilities was 54.9%,32 57.9%,27 and 57.3%,39 respectively. This finding was also consistent with a previous study report in Ethiopia where the level of good utilisation was 57.42% 40.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding was almost in line with a study finding in Hadiya Zone, Oromia Regional State, and Southwest Ethiopia, where utilisation of HMIS at health facilities was 54.9%,32 57.9%,27 and 57.3%,39 respectively. This finding was also consistent with a previous study report in Ethiopia where the level of good utilisation was 57.42% 40.…”
Section: Discussionsupporting
confidence: 91%
“…A study finding from Cote d’Ivoire and South Africa indicated that the overall percentages of HMIS information use were 38%24 and 53%,25 respectively. In Ethiopian context, the use of routine health information varied in different areas of the country and it is also considered as partial, not uniform, which is ranging from 32.9% to 78.5% 4 11 26–41…”
Section: Introductionmentioning
confidence: 99%
“…In this study, information use practice was less likely among trained health workers compared to untrained health workers. This finding was in contradiction to other studies that found RHI training was positively associated with proper information utilization [ 17 , 20 , 27 , 29 , 30 , 32 ]. In the study area, the majority of health workers were trained, with a higher proportion of them having received training before the 12 months of survey period and most had received RHI training with a component of data management and quality assurance.…”
Section: Discussioncontrasting
confidence: 99%
“…Likewise, health workers’ skill in data analysis and interpretation also showed a positive association, in which good information utilization was three times more likely among competent health workers in data analysis and interpretation. This finding was consistent with other studies [ 19 , 20 , 27 , 30 , 32 ]. Lack of skills to analyze, interpret, and use data among health workers impedes real-time decision making in organizations.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation